Comparative Analyzation of Criminal Law for Sexual Harassment Based on Awig-Awig and Law 12 of 2022: Analisis Perbandingan Hukum Pidana Pelecehan Seksual Berdasarkan Awig-Awig dan Undang-Undang 12 Tahun 2022 - Afra, Fairuz; Sumardiana, Benny (Faculty of Law Hang Tuah University, 2025)
Indonesia has two legal systems, customary law and national law, which often clash in sexual harassment cases. Bali's Awig-Awig promotes restorative justice, while Law No. 12 of 2022 emphasizes strict criminal sanctions. This difference can trigger conflict, especially regarding the rights of female victims. Therefore, this study will discuss how the mechanism between the two laws compares and which law is more effective in applying in sexual harassment cases in Bali. This research compares the effectiveness of the two legal systems using a socio-legal method and comparative approach. The results show that the integration of customary deliberation with formal legal protection can bridge such differences, ensuring culturally sensitive and comprehensive justice.